Increasing Students’ Learning Activities with the STAD Learning Model Combined with the Kokami Media on the Classification of Living Things - Yuniarti, Anisyah; Ningsih, Kurnia; Maudy, Fadhelia; Tahir, Norhayati (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
This study aimed to increase students’ learning activities using the Student Teams Achievement Division (STAD) learning model combined with Mysterious Card Box (Kokami) media on the material of classification of living things in class VII G at Junior High School. This study used Classroom Action Research (CAR). Data collection techniques used in this study were observation and documentation. The instrument used was an observation sheet. The subjects of this study were students of class VII G, totaling 35 people consisting of 19 girls and 16 boys. Indicators of students’ learning activities observed consisted of 5: visual, oral, listening, writing, and emotional. This study was conducted with two cycles and two meetings. In cycle I, the average percentage per cycle of students’ learning activities was 76.93% (good); in cycle II, it was 88.33% (very good). This shows that the percentage of learning activities has increased by 11.40%. Thus, using the STAD learning model combined with Kokami increased students’ learning activities. Meningkatkan Aktivitas Belajar Peserta Didik dengan Model STAD Dipadukan Media Kokami pada Materi Klasifikasi Makhluk Hidup ABSTRAK: Tujuan penelitian ini adalah untuk meningkatkan aktivitas belajar peserta didik menggunakan model STAD dipadukan media Kokami pada materi klasifikasi makhluk hidup di kelas VII G di SMPN. Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK). Teknik pengumpulan data yang digunakan dalam penelitian ini adalah observasi dan dokumentasi. Instrumen yang digunakan adalah lembar observasi. Subjek penelitian ini adalah peserta didik kelas VII G yang berjumlah 35 orang terdiri dari 19 perempuan dan 16 laki-laki. Indikator aktivitas peserta didik yang diamati terdiri 5, yaitu visual activities, oral activities, listening activities, writing activities, dan emotional activities. Penelitian ini dilaksanakan dengan 2 siklus dan 2 kali pertemuan. Pada siklus I, persentase rata-rata per siklus aktivitas belajar peserta didik sebesar 76,93% (baik) dan pada siklus II sebesar 88,33% (sangat baik). Hal ini menunjukkan bahwa pada persentase aktivitas belajar mengalami peningkatan sebesar 11,40%. Maka dari itu, penggunaan model STAD dipadukan media Kokami berhasil meningkatkan aktivitas belajar peserta didik.